Harnessing Therapeutic IgE Antibodies to Re-educate Macrophages against Cancer. Issue 6 (June 2020) - Pellizzari, Giulia; Bax, Heather J.; Josephs, Debra H.; Gotovina, Jelena; Jensen-Jarolim, Erika; Spicer, James F.; Karagiannis, Sophia N.
Abstract : Currently, IgG is the only class of antibodies employed for cancer therapy. However, harnessing the unique biological properties of a different class ( e.g., IgE) could engender potent effector cell activation, and unleash previously untapped immune mechanisms against cancer. IgE antibodies are best known for pathogenic roles in allergic diseases and for protective effector functions against parasitic infestation, often mediated by IgE Fc receptor-expressing macrophages. Notably, IgE possess a very high affinity for cognate Fc receptors expressed by tumor-associated macrophages (TAMs). This paper reviews pre-clinical studies, which indicate control of cancer growth by tumor antigen-specific IgE that recruit and re-educate TAMs towards activated profiles. The clinical development harnessing the antitumor potential of recombinant IgE antibodies in cancer patients is also discussed. Highlights: IgE antibodies engineered to recognize cancer antigens can activate host immunity and promote tumor killing. Different in vivo models of cancer demonstrate potential for therapeutic superiority of IgE compared to IgG1. In the presence of IgE engagement and immune complex formation, classically activated macrophages (M1) can retain their inflammatory and antigen-presenting profile, while alternatively activated macrophages (M2) are re-activated to express inflammatory markers. Macrophage activity in solid tumors treated with IgE is more similar to IgE-mediated physiological protective functions in antiparasitic immunity than to an allergic immune response. The first monoclonal IgE antibody engineered to target a tumor-associated antigen is now under clinical development in cancer patients.